1991
DOI: 10.1111/j.1469-8986.1991.tb00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tonic Parasympathetic Cardiac Control Using Respiratory Sinus Arrhythmia: The Need for Respiratory Control

Abstract: Respiratory sinus arrhythmia (RSA) has received much attention in recent years due to the large body of evidence indicating that variations in this phenomenon represent alterations in parasympathetic cardiac control. Although it appears that respiratory sinus arrhythmia is mediated by vagal mechanisms, the extent to which the well-known respiratory influences (i.e., rate and tidal volume) on respiratory sinus arrhythmia (in altering its magnitude) may moderate the relationship between RSA and cardiac vagal ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
320
1
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 431 publications
(333 citation statements)
references
References 34 publications
7
320
1
5
Order By: Relevance
“…It is noted that the HF component of HR variability, which was the main target of this study, has been reported to be dependent on the breathing cycle and to be affected by breathing rate and tidal volume [22][23][24][25]. Only one earlier study has investigated the effects of TP massage on autonomic nervous activity and reported an increase in parasympathetic nervous activity based on spectral analysis of HR variability [17].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is noted that the HF component of HR variability, which was the main target of this study, has been reported to be dependent on the breathing cycle and to be affected by breathing rate and tidal volume [22][23][24][25]. Only one earlier study has investigated the effects of TP massage on autonomic nervous activity and reported an increase in parasympathetic nervous activity based on spectral analysis of HR variability [17].…”
Section: Introductionmentioning
confidence: 88%
“…These findings suggest that relative activity of parasympathetic nervous system was increased. However, the HF component of HR variability has been reported to be dependent on the respiration cycle and affected by respiration frequency and tidal volume [22][23][24][25]. Burst firing of the parasympathetic nerve (vagal nerve) disappears or decreases during inspiration, and the HR variability associated with the disappearance or decrease of the burst firing is observed as the HF component (i.e., respiratory sinus arrhythmia).…”
Section: Effect Of Pressure Application Over Tps On Autonomic Activitymentioning
confidence: 99%
“…It is known that both tidal volume and breathing frequency may affect high frequency component of HRV at rest. Increased tidal volume has been found to increase HRV, whereas increased breathing frequency decreases it (Grossman et al 1991;Keselbrener & Akselrod 1996). However, Bartels et al (2004) suggested that HFP during exercise presents true cardiovascular vagal modulation instead of being affected by changes in ventilation.…”
Section: Limitationsmentioning
confidence: 99%
“…Measured as the peak-valley difference in R-R intervals associated with breathing (Grossman and Wientjes, 1986). Highly correlated with high-frequency heart rate variability spectral power (0.15-0.40 Hz), but less susceptible to misestimation during slow breathing (Grossman et al, 1991) HF power High-frequency heart rate variability spectral power (0.15-0.40 Hz); reflects parasympathetic influences on the cardiovascular system LF power Low frequency heart rate variability spectral power (0.04-0.15 Hz); reflects both sympathetic and parasympathetic influences on the cardiovascular system and is strongly associated with blood pressure regulation (Kamath et al, 1987) VLF power Very low frequency heart rate variability spectral power (0.0033-0.04 Hz); in addition to sympathetic and parasympathetic inputs, may be influenced by the thermoregulatory, peripheral vasomotor, and renin-angiotensin systems (Kamath et al, 1987) ULF power Ultra low frequency heart rate variability spectral power (1.15!10 K5 -0.0033 Hz); reflects circadian and other long-term variations in heart rate (Kamath et al, 1987) LF/HF ratio Ratio of low-to high-frequency power; a disputed measure of sympathovagal balance (Kouakam et al, 1999) Pulse wave transit time to the finger (PTT) Putative non-invasive measure of general cardiovascular sympathetic influences; related to cardiac contractility, blood pressure, and arterial tone (Weiss et al, 1980) Blood volume pulse (BVP) Measured as the difference between peak and valley of the peripheral pulse waveform. Reflects peripheral vasoconstriction, an a-adrenergic sympathetic measure (Miller and Ditto, 1991) PO 2 Clinical measure of arterial oxygen saturation.…”
Section: Vivologic Physiologic Data Analysis and Displaymentioning
confidence: 99%
“…Both tidal volume (quantifying the depth of each breath) and respiratory rate changes can seriously distort the relationship between vagal activity and RSA (Grossman et al, 1991). Recently, algorithms have been proposed that employ continuously measured respiratory parameters to reduce this distortion Wilhelm et al, 2004).…”
Section: Introductionmentioning
confidence: 99%